Updating the national checklist of marine fishes in Spanish waters: An approach to priority hotspots and lessons for conservation - BÁEZ, JOSÉ CARLOS; RODRÍGUEZ-CABELLO, CRISTINA; BAÑÓN, RAFAEL; BRITO, ALBERTO; FALCÓN, JESÚS M.; MAÑO, TOÑO; BARO, JORGE; MACÍAS, DAVID; MELÉNDEZ, MARÍA JOSÉ; CAMIÑAS, JUAN ANTONIO; ARIAS-GARCÍA, ALBERTO; GIL, JUAN; et al. (Mediterranean Marine Science, 2019)
In response to a request from the Spanish Ministry of Farming, Fishing, Food, and Environment (Spanish: Agricultura, Pesca, Alimentación y Medio Ambiente) in 2015, a fish expert group was formed to provide a reference list of marine fish species according to five regions (marine demarcations) established by Spanish Law 41/2010 on the protection of the marine environment. The objective of this article was to update and analyse the data compiled in the marine fish species checklist in order to: 1) provide a complete list of marine fish species in the Spanish Exclusive Economic Zone; 2) compare this checklist between bio-geographical areas; and 3) identify possible priority hotspots for their conservation. We applied several indices, such as the total number of species in each area, species richness, and the Biodiversity Conservation Concern index. We discuss gaps in knowledge and the lessons learned for conservation purposes. A total of 1075 marine fishes were reported in Spanish waters. Most of these fish were well determined, whereas a few were treated as uncertain. The marine demarcation with the most species is the Canary Islands with 795 species, followed by the Spanish north coast demarcation with 506 species. However, the marine demarcations with the most species per area are the Spanish coast of the Gulf of Cádiz and the Strait of Gibraltar-Alboran Sea.